A prominent dual heterojunction framed CuWO4/Bi2WO6/MnS ternary NCs for para-chlorophenol degradation, Cr(VI) reduction & toxicity studies. (September 2022) - Subhiksha, V.; Okla, Mohammad K.; Alaraidh, Ibrahim A.; Mohebaldin, Asmaa; Soufan, Walid; Abdel-Maksoud, Mostafa A.; Abdelaziz, Ramadan F.; Thomas, Ajith M.; Raju, Lija L.; Khan, S. Sudheer
Abstract: In account of environmental remediation, an ideal photocatalyst was fabricated for the effective treatment of water systems. Herein, dual heterojunctions framed CuWO4 /Bi2 WO6 /MnS nanocomposite (NCs) was synthesized via simple co-precipitation method followed by ultra-sonicated assisted route. The prepared NCs were investigated its photocatalytic degradation performance using para -chlorophenol (4-CP) and reduction of chromium VI (Cr (VI)) under visible light irradiation. The photocatalyst were characterized by various analytical techniques including XRD, HR-TEM, XPS, UV–vis DRS, FE-SEM, EIS, PL, ESR, Raman and N2 adsorption and desorption studies. The excellent photodegradation of 4-CP was observed within 180 min by the NCs. Similarly, the Cr (VI) reduction was about 97% within 140 min. The effect of pH and influence of different dosage of NCs and 4-CP on the photodegradation efficiency was investigated. The reusability and stability of the NCs was examined over 6 consecutive runs where the XRD and XPS confirm the structural stability of the prepared NCs. The scavenging experiment were carried out to elucidate the mechanism and the active species involved were O 2− and OH radicals. The TOC analysis affirmed the complete mineralization of the prepared NCs. The ecotoxicity analysis was carried out to determine the toxicity effect of intermediates using ECOSAR software and the end product toxicity was also evaluated against E. coli and S. epidermis . The end product toxicity study also confirmed that the degraded product was less toxic compared to parent compound. Further, the genotoxicity study was done to understand the environmental impact using allium cepa and results confirms that there are no causes of cytotoxicity & genotoxicity by the prepared NCs. Therefore, the prepared NCs can be economical, efficient with excellent photocatalytic performance and environment friendly. Graphical abstract: Image 1 Highlights: CuWO4 /Bi2 WO6 /MnS NCs was synthesized via simple co-precipitation and ultra-sonication assisted method. The excellent photodegradation of p -chlorophenol was observed within 180 min. The NCs exhibited good photocatalytic reduction of Cr(VI) within 140 min. The end product toxicity was evaluated against E. coli and S. epidermis . The phytotoxicity study was performed using Allium cepa .